Titania-based organic-inorganic hybrid planar waveguides - Nassar, E. J.; Goncalves, R. R.; Ferrari, M.; Messaddeq, Younes [UNESP]; Ribeiro, SJL (Elsevier B.V., 2002)
Eu3+ -doped titania-silica planar waveguides were prepared from tetraethylorthotitanate (TEOT) and modified silane 3-amino-propyltriethoxysilane (APTS). Films were deposited on borosilicate glass substrates by a dip-coating technique. The refractive index, the thickness and the total attenuation coefficient of the waveguides were measured at 632.8 and 1550 nm by prism coupling technique. Starting from pure titania films, the addition of modified silane leads to a decrease in the refractive index and an increase in thickness. Squared electric field simulation has shown that the light confinement in the waveguide increases with the silane content of the so]. Emission spectra present a broad emission band due to the modified silane and EU emission transitions arising mainly from the D-5(0) level to the F-7(J) (J = 0-4) manifolds. The dependence of transition intensities and excited state lifetimes on the initial composition and also on the heat treatment performed was interpreted in terms of structural changes occurring during the preparation process. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: sol-gel; europium(III); luminescence; thin films; planar waveguides